Sustainable Development of Micro, Small and Medium Enterprises (MSMEs) Through Marketing Mix and Digital Marketing - Wasito; Sadikun Citra Rusmana; Muhammad Iqbal Baihaqi; Din Muhammad Kautsar (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to describe the swot analysis and promotion mix for MSMEs in Karang Tengah Village, Kadungora District, Garut Regency. The object of this research is the Mayit Cake Traditional Food SMEs operating in Karang Tengah Village, Kadungora District, Garut Regency. The research method used is the Qualitative Descriptive Research Method which aims to describe the conditions that exist in the research object of MSME actors. The marketing mix that occurs in the research object. Data analysis techniques used in qualitative descriptive research are interviews, observations, literature studies and focus group discussions. The SWOT analysis method identifies that internal-external factors greatly influence the company's strategic objectives. The results of the research using the SWOT analysis method in this study there are 4 exposures, namely the IFAS matrix description which states that the Strength factor has a score of 3.65 while the Weaknesses have a score of 3.45. Whereas the EFAS matrix states that the Opportunity factor produces a value with a score of 3.70, while for Threats it has a score of 3.30. From the two results of the SWOT analysis, it shows that the kue mayit product is in quadrant I, this is because the difference produces a positive value and has a good weight on the strength factor and the opportunity factor. As for the results of the IE matrix analysis, the cake mayit product is in cell I which has a company condition that is assessed as Grow and Build. There are various forms of strategy in increasing sales of kue mayit products. So it can be concluded that the kue mayit product business needs to use or implement a Strengths Opportunities strategy where this strategy uses the company's internal strengths to seize opportunities that exist outside the company.